Penerapan Kegiatan Montase Untuk Meningkatkan Motorik Halus AUD Di PAUD Harapan Bunda Desa Kasih Raja - Claulia Natasya; Ismah Namirah Noor Faizah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
. Early childhood education (ECED) is a very important early stage in a child's development. During this period, children experience rapid cognitive, social and motor development. Fine motor skills are very important in child development, as they have a positive impact on a child's ability to write, draw, and perform other daily tasks. The application of montage activities at PAUD Harapan Bunda Desa Kasih Raja is an effective step in improving the fine motor skills of early childhood. Montage is a visual art technique that involves combining small pieces of material such as paper, cloth, or other objects into a single image or design. Montage activities can help children develop their fine motor skills while stimulating their creativity. In this activity, children will learn to control their hand movements to cut, paste and arrange the materials with precision. The application of montage activities aims to improve children's fine motor skills at PAUD Harapan Bunda Desa Kasih Raja Lubuk Keliat. This research method uses descriptive qualitative research with data collection in the form of observation and documentation. From the results of observations, researchers show that montage activities are very influential in improving children's fine motor skills at PAUD Harapan Bunda Desa Kasih Raja Lubuk Keliat.